Knowledge of Health Workers in the Implementation of Islamic Health Based on Islamic Hospital Accreditation Standard - Zulkahfi Zulkahfi; Irwan Hadi; Tukimin bin Sansuwito; Norhanita Zaini (Indonesian Journal of Global Health Research, 2024)
The knowledge of health workers about the implementation of Islamic health in hospitals is the most dominant factor in improving the quality of health services. The implementation of Islam can be carried out if the knowledge of health workers increases. Objective to find out the overview of the knowledge of health workers in the implementation of Islamic health based on Islamic hospital accreditation standards. This type of research is a quantitative research with an analytical descriptive research design with a cross sectional approach, with a sample number of 82, sampling techniques using purposive sampling. Data collection uses questionnaires. Based on gender, the most women are 53 people (64.6%), the most education is at the intermediate expert level as many as 35 people (42.7%). Respondents had knowledge with a good category as many as 43 people (52.4%), attitude with a good category as many as 58 people (70.7%), leadership with a good category as many as 70 people (85.4%), workload with a good category as many as 78 people (95.1%), facilities with a good category as many as 79 people (96.3%), and implementing Sharia Quality Standards with a good category as many as 59 people (72.0%). This study shows that the Implementation of Islamic Health in accordance with the accreditation standards in Islamic Hospitals shows that it is categorized as Good.